Nano- And Micro-Particle Drug Delivery Systems For Enhancing The Bioavailability Of Anti-Diabetic Agents - Patil, Anasuya; Nautiyal, Akhilesh; Gupta, Abhilasha; Kumar Singh, Asheesh; Singh, Prashant; Tomar, Anshika; Kumar, Shubham; Chiangkata, Replantful; Alam, Shakeel (Journal of Neonatal Surgery, 2025)
Diabetes mellitus, particularly type 2 diabetes (T2DM), remains a global health challenge characterized by chronic hyperglycemia and associated complications. Conventional anti-diabetic therapies often face limitations such as low bioavailability, frequent dosing requirements, systemic side effects, and drug resistance. Nano- and micro-particle drug delivery systems have emerged as promising strategies to overcome these obstacles by improving the pharmacokinetic and pharmacodynamic profiles of anti-diabetic agents. These delivery platforms, including polymeric nanoparticles, lipid-based carriers, vesicular systems, inorganic nanoparticles, and nanosuspensions, offer enhanced drug stability, targeted delivery, sustained release, and reduced toxicity. Moreover, they facilitate improved oral absorption by protecting drugs from gastrointestinal degradation and bypassing first-pass metabolism via lymphatic transport. Encapsulation of both synthetic drugs and natural phytocompounds in nano- and micro-carriers significantly augments their therapeutic efficacy, bioavailability, and patient compliance. Despite substantial preclinical evidence, clinical translation remains limited due to concerns about toxicity, complex synthesis, and stability challenges. This review highlights recent advancements in particle-based drug delivery technologies for anti-diabetic agents, emphasizing their mechanisms, benefits, and existing barriers. Continued research and clinical evaluation are imperative to fully realize the potential of nano- and micro-particle systems in enhancing diabetes management and patient outcomes (2020).